Variability of the origin and course of the uterine artery in clinical practice - Sobolewska, Adela; Gierulska, Natalia; Stachowicz, Hubert; Iwaniuk, Kaja; Białkowska, Zuzanna; Daniluk, Aleksander; Ostański, Jan; Buczek, Jakub; Samczuk, Maciej; Gawłowicz, Łukasz (Journal of Education, Health and Sport, 2024)
In 2020, approximately 287,000 mothers died during pregnancy or childbirth, with one of the leading causes of maternal mortality being peripartum hemorrhage. It can be treated both pharmacologically and procedurally, for example, through uterine artery ligation, embolization, or hysterectomy. In case of procedural treatment, it is essential for the medical team to familiarize themselves with the anatomical structure of the patient’s uterine arteries. Various variations in the course of this vessel are distinguished, such as the uterine artery branching as a bifurcation with the inferior gluteal artery, a common trunk of the uterine artery with another vessel, or even its duplication. Using radiological techniques such as angiography, it is possible to visualize vessels and their variations, which can allow for better patient care. Unfamiliarity with the departure and trajectory of the uterine artery may be associated with an increased risk of postoperative complications, especially after hysterectomy, where the uterine arteries close at the level of the uterus or at the beginning of their departure from the internal iliac artery. Ligating them in other place may result in ischemia of an area that should be continuously supplied with blood. Also, during surgery, special attention should be paid to possible anatomical variations of the patient’s uterine artery, which, although rare, can cause intraoperative complications. A thorough analysis of the departure and trajectory of the uterine artery by physicians can prevent postoperative complications and also allow for the safe conduct of embolization procedures. The following article presents a literature review on the departure and course of the uterine artery and its variations, as well as procedural interventions related to this vessel.